Oceanic feelings and their relationship to spirituality and personality organization - Straßnig, Sarah; Herzl, Tobias; Latifi, Afrodita; Fuchshuber, Jürgen; Jimenez, Paul; Unterrainer, Human-Friedrich (Frontiers in Psychology, 2025)
BackgroundOceanic feelings, which reflect a sense of boundlessness, unity but also fragmentation can evoke spiritual experiences and possibly lead to psychosis proneness. This study explores oceanic feelings psychometrically, by examining their connections with spirituality, schizotypy, and personality organization.MethodsA sample of 480 adult non-clinical participants (66.2% female) completed an online survey, which included the Oceanic Feeling Scale, the MI-RSWB-18, SPQ-B, and the IPO-16. All relationships were evaluated in a path analysis to assess the direct and indirect effects of positive and negative oceanic feelings on schizotypy, connectedness, and general religiosity, with personality organization as a mediator.ResultsPositive oceanic feelings were strongly correlated with increased connectedness (r = 0.68) and general religiosity (r = 0.61). We measured weak to moderate associations of negative oceanic feelings with schizotypy (r = 0.41) and personality organization (r = 0.39). Path analysis revealed that personality organization mediated the relationship between negative oceanic feelings and schizotypy (β = 0.11, p < 0.001). Additionally, the relationship between negative oceanic feelings and general religiosity was also fully mediated by personality organization (β = 0.05, p < 0.011). The association between negative oceanic feelings and connectedness was partially mediated by personality organization (β = 0.07, p < 0.001).DiscussionThe findings reveal a dual role of oceanic feelings: positive oceanic feelings enhance general religiosity and connectedness independently of personality organization, while negative oceanic feelings are mediated by personality dysfunction, influencing schizotypy and spirituality. Strengthening personality organization could serve as a protective factor against the destabilizing effects of negative oceanic experiences, offering insights for psychotherapy and spiritual counselling.